Debtor (non-) participation in sovereign debt relief: A real option approach - Danny Cassimon; Dennis Essers; Andrea Presbitero (National Bank of Belgium, 2023)
Developing countries have recently proved reluctant to participate in sovereign debt moratoria and debt relief initiatives. We argue that debtors' (non-)participation decisions can be understood through the lens of real options. Eligible countries compare the net benefits of participating in a debt relief initiative now with the value of waiting to potentially execute their participation option later, when they may have more information on the benefits and costs. We corroborate the real option framing with anecdotal evidence and through a survival analysis that exploits cross-country and time variation in the requests to participate in the Debt Service Suspension Initiative (DSSI), which provided temporary debt moratoria during the COVID-19 pandemic. Structured along the policy levers suggested by the real option framework, we discuss a number of ways in which participation in debt relief initiatives can be made more attractive to debtor countries.
Keywords: H63; F34; F55; 330; sovereign debt; sovereign debt relief; Debt Service Suspension Initiative; Common Framework; real options; survival analysis